MODERN PROHIBITION OF NON LIQUET AND THE EXCEPTION: CONTINGENCY FORMULA FOR DECISION AND DEVELOPMENT OF THE PARADOXES OF THE LEGAL SYSTEM - Rocha, Leonel Severo; Pinto, João Paulo Salles (Revista da Faculdade de Direito do Sul de Minas, 2026)
This article argues that the modern prohibition of non liquet operates as a semantic contingency formula through which the legal system manages the paradox of decision and preserves its functional differentiation. Grounded in a pragmatic-systemic methodological framework and drawing on Niklas Luhmann’s theory of autopoietic social systems, the study maintains that courts occupy a structurally exceptional position because they are obliged to decide even where legal determination appears impossible. This obligation transforms undecidability into institutionalized decidability, converting paradoxical indeterminacy into communicative continuity. By revisiting the historical evolution of non liquet, from Roman law to modern codifications, and engaging contemporary debates on exceptionality, the article demonstrates that exception is not merely a political category but an operative presupposition of judicial decision-making. The prohibition of denial of justice thus functions as a mechanism that invisibilizes paradox while reinforcing organizational autonomy and systemic closure. Key words: Prohibition of non liquet; Legal system; Paradoxes; Judicial Decision; Luhmann’s theory.